1984
DOI: 10.1111/j.2164-4918.1984.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Measured Effects of Primary Prevention Strategies

Abstract: A meta‐analysis of 40 primary prevention studies provided an encouraging assessment of past efforts and clear challenges for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…For example, the two that focused on primary prevention programs indicated that participation in primary prevention programs is helpful to students (Baker, Swisher, Nadenichek, & Popowicz, 1984;Sprinthall, 1981). In one of those, Baker Electronic Journal: To print this article select pages 44-58.…”
mentioning
confidence: 99%
“…For example, the two that focused on primary prevention programs indicated that participation in primary prevention programs is helpful to students (Baker, Swisher, Nadenichek, & Popowicz, 1984;Sprinthall, 1981). In one of those, Baker Electronic Journal: To print this article select pages 44-58.…”
mentioning
confidence: 99%
“…Many managed-care companies currently pay for annual well-care visits, vaccinations, and other services in support of preventive medicine, but they do not support the provision of preventive mental health care. There is extensive evidence indicating that mental health professions can ward off adjustment difficulties in children by replicating the clinical procedures that have been used in model prevention programs (Baker & Shaw, 1987;Baker, Swisher, Nadenichek, & Popowicz, 1984;Greenberg, Domitrovich, & Bumbarger, 2001). We must convince Congress that preventing schoolwide bullying, school drop out, or teenage parenthood is as important as preventing the flu and that our nation has a responsibility for promoting the holistic well-being of its people through an expansion of compensated mental health services, including preventive mental health services (Kiselica, 2001b).…”
Section: The Mental Health Professions Must Lobby For Policies That Cmentioning
confidence: 99%
“…(p. xiv) Critics of get-tough disciplinary practices also point to the availability of potentially more effective alternative interventions, such as peermediation (Carruthers, 1996;Johnson and Johnson, 1996;Kamps and Tankersley, 1996). Baker, Swisher, Nadenichek and Popowicz (1984) conducted a review of the literature on the various types of childcentered aggression primary prevention intervention programs. In their review they found the overall effect size associated with communication skills training was large (.93).…”
Section: Journal Of Social Service Researchmentioning
confidence: 99%